Preparation and physicochemical characterization of whitlockite/PVA/Gelatin composite for bone tissue regeneration - Batool, Sadaf; Liaqat, Usman; Hussain, Zakir (Frontiers in Chemistry, 2024)
This work used a straightforward solvent casting approach to synthesize bone whitlockite (WH) based PVA/Gelatin composites. WH nanoparticles (NPs) were synthesized using the wet precipitation method, followed by their addition into the PVA/Gelatin matrix at concentrations from 1 % to 10 %. The physicochemical characterization of the prepared PVA/Gelatin/WH composite was carried out using ATR-FTIR, Optical profilometry, a Goniometer, a Universal tensile testing machine (UTM), and sScanning electron microscopy (SEM) techniques. The ATR-FTIR analysis confirmed the formation of noncovalent interactions between polymeric chains and WH NPs and the incorporation of WH NPs into the polymer cavities. SEM analysis demonstrated increased surface roughness with the addition of WH NPs, supporting the results obtained through optical profilometry analysis. The mechanical properties of the prepared composite showed an increase in the tensile strength with the addition of WH filler up to 7 % loading. The prepared composite has demonstrated an excellent swelling ability and surface wettability. The reported results demonstrate the exceptional potential of the prepared composite for bone tissue regeneration.